Nilai Perusahaan Ditinjau Menggunakan Green accounting, Kinerja Lingkungan dan Pertumbuhan Laba - Gisca Dwi Desriyunia; Nera Marinda Machdar (Pusat Riset dan Inovasi Nasional, 2025)
The development of the business world in developing countries encourages companies to increase company value by improving their reputation in the eyes of the public. One important step in this effort is to increase profits and demonstrate responsibility towards the environment and society. This research aims to find and analyze theories that discuss the influence of green accounting, environmental performance and profit growth on company value. This research uses the literature review method to analyze and present the reasons behind the explanatory variables, as well as findings from previous research. The theories behind this research are agency theory and signal theory. Variables that are thought to influence company value include green accounting, environmental performance, and profit growth. The research results show that the relationship between green accounting, environmental performance and profit growth on company value varies, so a clear agreement has not been reached. This study provides a detailed picture based on existing facts and can be a reference for further research that uses green accounting, environmental performance and profit growth variables.